Single-port non-lipolytic endoscopic surgery via the axillary approach for the treatment of benign breast tumors has better clinical outcomes: a case control study - Tianyi Ma; Jian Cui; Qian Wang; Changgen Liu; Bin Wang; Haibo Wang (BMC Women's Health)
Abstract Background Endoscopic surgery provides good cosmetic results while ensuring therapeutic outcomes. This study aimed to evaluate the efficacy, safety, and cosmetic outcome of endoscopic surgery for benign breast tumors. Methods In total, 108 patients were enrolled and divided into endoscopic or open surgery groups based on the patients' voluntary decisions. Surgical information, complications, postoperative pain, and postoperative cosmetic scores were compared. Results The endoscopic surgery group and open surgery group included 46 and 62 patients, respectively. Patients who underwent endoscopic surgery had longer operative times (p < 0.001) and postoperative hospital stays (p = 0.045), and there was no significant difference in intraoperative blood loss between the two groups (p = 0.501). The overall postoperative complication rate was 13% in the endoscopic group and 25.8% in the open group (p = 0.103). Postoperative pain scores were similar in both groups. Cosmetic scores were better in the endoscopic group (p = 0.002), especially regarding nipple shape and wound scarring. Conclusions Endoscopic surgery is safe and effective for treating benign breast tumors and offers improved cosmetic results compared to open surgery.